Tracer sedimentation equilibrium: a powerful tool for the quantitative characterization of macromolecular self- and hetero-associations in solution. (1st October 2003) - Rivas, G.; Minton, A.P.
Abstract : During the last two decades the measurement and analysis of sedimentation equilibrium has been used increasingly as a method for characterizing intermolecular interactions in solution. More recently, a variant of this technique has been developed, in which a trace amount of a single solute component is labelled so that the concentration gradient of that component at sedimentation equilibrium may be measured independently of the gradients of all other components. The dependence of equilibrium tracer gradients upon solution composition may be readily interpreted in the context of models for self- and hetero-association of the labelled component, and, in the case of concentrated solutions, repulsive as well as attractive solute–solute interactions. We present a summary of experimental and analytic methods, a brief review of some previously published applications, and a preview of new applications demonstrating capabilities beyond those afforded by other current techniques for characterizing macromolecular associations in solution.